Commercial Alum/PEG 400 Catalyzed Efficient Synthesis of Substituted 2-Phenyl-4H-chromen-4-ones by Microwave Irradiation - S. DAVE, SHIKHA; M. RAHATGAONKAR, ANJALI (Asian Journal of Chemistry, 2010)
Commercial alum/PEG 400 catalyzed, an alternate and efficient synthesis of appropriately substituted 2-phenyl-4H-chromen-4-ones by microwave irradiation has been reported here. In this one pot reaction, maximum atom economy was achieved; reaction time was highly reduced from hours to seconds and hence it is claimed that this methodology as an environmentally benign procedure.